The Impact of Serving Leadership, Team Work on Higher Education Performance - Marampa, Adriana Madya; Pali, Elisabeth; Lestari, Raden (Faculty of Economics and Business, Jenderal Soedirman University, 2023)
The purpose of this study was to find out how servant leadership influences team work, how team work influences organizational performance and how servant leadership influences the performance of a tertiary institution. The population in this study are campuses in South Sulawesi. The sample of this research is 54 lecturers in one of South Sulawesi. The sampling technique was carried out by simple random sampling. Data processing method using SEM-PLS. The novelty of this research is that research on team work with the dimensions of togetherness, trust, emotional closeness, empathy has not been studied much, especially in higher education.The results showed that the relationship between Team Work (X1) and Performance (Y) was significant with a T-statistic of 2,149 (> 1.96).). Thus the H1 hypothesis is accepted. The results showed that the relationship between Servant Leadership (X2) and Performance (Y) was significant with a T-statistic of 2.145 (>1.96). Thus the H2 hypothesis was accepted. The results showed that the relationship between Servant Leadership (X1) and Team Work (X2) was significant with a T-statistic of 52,645 (> 1.96).Thus the H3 hypothesis is accepted. The results showed that there was a significant relationship between Team Work (X1) and Performance (Y) through Leadership (X2) with a T-statistic of 2,027 (> 1.96). The relationship between variables can be considered significant if the P value is smaller than the predetermined significant value (0.000 <0.05). Thus the H4 hypothesis is accepted.